2019
DOI: 10.1002/jctb.6039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ag/titanate nanotubes on physicochemical, antifouling and antimicrobial properties of mixed‐matrix polyethersulfone ultrafiltration membranes

Abstract: BACKGROUND: One of the main drawbacks of membrane processes is (bio)fouling. Recent attempts to overcome these phenomena focus on incorporation of nanoparticles into polymeric membrane matrices. This paper presents an investigation of the influence of modification of polyethersulfone (PES) ultrafiltration membranes with Ag/titanate nanotubes (Ag/TNTs) on physicochemical characteristics, water permeability and antifouling and antibacterial properties.RESULTS: The modified membranes were prepared via a wet phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 95 publications
(172 reference statements)
1
12
0
Order By: Relevance
“…Membrane processes have also been applied on a full scale and are the most used technology for EC treatment thanks to different processes and a wide range of membrane materials, depending on the leading separation mechanism of the membrane and targeted pollutant [ 38 , 39 , 40 ]. Moreover, some membranes combine other properties together, such as sorption capacity, degradation ability, and antifouling properties [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane processes have also been applied on a full scale and are the most used technology for EC treatment thanks to different processes and a wide range of membrane materials, depending on the leading separation mechanism of the membrane and targeted pollutant [ 38 , 39 , 40 ]. Moreover, some membranes combine other properties together, such as sorption capacity, degradation ability, and antifouling properties [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 presents a schematic illustration of localized MIC on aluminum alloy, according to the concepts described in [14]. [14] The beneficial properties of silver and its ions are not limited only to their confirmed bactericide properties, recently widely investigated [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Materials, containing this element possess also definitively catalytic [41][42][43] and photocatalytic [44][45][46][47][48][49][50][51][52][53][54][55][56][57] properties.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment methods were not adequate to treat pharmaceutical wastewater 4–6 . In recent decades, among the various advanced oxidation processes (AOPs), photocatalysis has been widely utilized in wastewater treatment and plays a vital role in water remediation 7–16 . Literature has reported that a wide range of semiconductor photocatalysts, such as TiO 2 , ZnS, Fe 2 O 3 , CdS, GaP, and ZnO, have proven their efficacy by degrading various organic pollutants in the presence of light 8–16 .…”
Section: Introductionmentioning
confidence: 99%